2021
DOI: 10.3389/fcell.2021.695021
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy Associated With Dermatan Sulfate-Deficient Decorin and Myostatin in Musculocontractural Ehlers-Danlos Syndrome: A Mouse Model Investigation

Abstract: Carbohydrate sulfotransferase 14 (CHST14) encodes dermatan 4-O-sulfotransferase 1, a critical enzyme for dermatan sulfate (DS) biosynthesis. Musculocontractural Ehlers-Danlos syndrome (mcEDS) is associated with biallelic pathogenic variants of CHST14 and is characterized by malformations and manifestations related to progressive connective tissue fragility. We identified myopathy phenotypes in Chst14-deficient mice using an mcEDS model. Decorin is a proteoglycan harboring a single glycosaminoglycan chain conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In 2021, Nitahara-Kasahara et al demonstrated that elephant teeth, thoracic kyphosis, increased skin fragility, and a kinked tail were observed in Chst14 -/mice [135,136]. Moreover, they also found a reduction in DS disaccharide in muscle and myopathy-related phenotypes including spread of the muscle interstitium and variation in fiber size, which may lead to decreased exercise capacity and lower grip strength in Chst14 -/mice.…”
Section: Knockout Mice Of Chst14/d4st1mentioning
confidence: 99%
“…In 2021, Nitahara-Kasahara et al demonstrated that elephant teeth, thoracic kyphosis, increased skin fragility, and a kinked tail were observed in Chst14 -/mice [135,136]. Moreover, they also found a reduction in DS disaccharide in muscle and myopathy-related phenotypes including spread of the muscle interstitium and variation in fiber size, which may lead to decreased exercise capacity and lower grip strength in Chst14 -/mice.…”
Section: Knockout Mice Of Chst14/d4st1mentioning
confidence: 99%
“…DSE and CHST14 encode DSE and dermatan 4-O-sulfoteransferase (D4ST), respectively, which function to biosynthesize DS [25][26][27]. Both knockout mice exhibited similar phenotypes such as skin fragility, thoracic kyphosis, and spina bifida, to patients with EDS of the musculocontractural type [28][29][30][31][32]. Therefore, DS is an indispensable macromolecule for the normal development of various tissues.…”
Section: Figurementioning
confidence: 99%
“…Chst14 -/mice exhibited elephant teeth, a kinked tail, increased skin fragility, and thoracic kyphosis, compared with Chst14 +/+ mice [29,31]. Moreover, Nitahara-Kasahara et al demonstrated that decreases in DS in muscle in addition to myopathy-related phenotypes such as variation in fiber size and spread of the muscle interstitium which caused lower grip strength and decreased exercise capacity, were observed in Chst14 -/mice compared with Chst14 +/+ as well as Chst14 +/mice [31,32].…”
Section: Chst14mentioning
confidence: 99%
“…(132,133) Furthermore, Chst14 -/mice showed thoracic kyphosis, and myopathy-related phenotypes such as lower grip strength and decreased exercise capacity, with decreased DS in muscle and variation in fiber size and spread of the muscle interstitium. (132,134) Additionally, Chst14 -/mice provided evidence for an overall negative impact of DS on peripheral nerve regeneration (131) but beneficial activity in central nervous system regeneration, which could result from differences in DS proteoglycans levels and their interaction partners between the peripheral and central nervous systems. ( 135) Chst14 -/mice also showed impaired spatial learning and memory and demonstrated that DS is indispensable for synaptic plasticity in the hippocampus, which might be attributed to impaired Akt/mTOR-signalling.…”
Section: Mceds-chst14mentioning
confidence: 99%